2017
DOI: 10.1080/0142159x.2017.1394998
|View full text |Cite
|
Sign up to set email alerts
|

Preparing teachers for competency-based medical education: Fundamental teaching activities

Abstract: Designed to support and aid teachers and those charged with faculty development, the Fundamental Teaching Activities Framework holds promise for all teachers in health sciences education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 16 publications
2
50
0
3
Order By: Relevance
“…Game-based teaching and learning is a participatory educational approach in which students brainstorm together to solve problems. Studies indicated that teaching activities involving games stimulate active learning and enhance learning motivation and outcomes [5,[21][22][23][24].…”
Section: Game-based Teachingmentioning
confidence: 99%
See 3 more Smart Citations
“…Game-based teaching and learning is a participatory educational approach in which students brainstorm together to solve problems. Studies indicated that teaching activities involving games stimulate active learning and enhance learning motivation and outcomes [5,[21][22][23][24].…”
Section: Game-based Teachingmentioning
confidence: 99%
“…Gee [25,26] stated that a successful game-based teaching approach features the following characteristics: (1) Identification, wherein participants establish a sense of identification in the game; (2) interaction; (3) risk-taking, that is, compared with real life, failing in a game does not incur serious consequences, thereby giving participants the freedom to take risks; (4) autonomy, that is participants have control over the game; (5) well-ordered problems, that is, the game is properly designed to include problems that are related and that enable participants to gradually grow and develop; (6) challenging, whereby the game is designed to have problems that challenge the existing professional knowledge of students; (7) instant feedback, whereby students instantaneously obtain necessary information to improve their ability of critical thinking; (8) situated and meaningful learning, that is, students can learn new concepts through game scenarios; (9) pleasantly frustrating; (10) exploration, in-depth understanding, and rethinking, whereby the game forces players to expand contextual knowledge to conduct comprehensive and in-depth thinking; (11) opportunities and environment for team-work; and (12) problem-based learning, where game-based teaching is also a type of problem-based learning which develops the problem-solving abilities of students. The instant feedback from the game helps students to improve and apply their problem-solving skills.…”
Section: Game-based Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…Steinert has defined struggling learners as medical trainees who do “not meet the expectations of a training program” 2. Such trainees, who experience more difficulties, often pose an even greater challenge to clinical teachers, since these learners warrant closer supervision,3 which may be time-consuming and compete with time spent on patient care, but may also require specific teaching skills 4. As a result, the supervision of struggling learners has been associated with reactions from clinical teachers ranging from helplessness to frustration and avoidance,2,5 as clinical teachers often perceive that they are ill equipped to supervise these learners efficiently 6…”
Section: Introductionmentioning
confidence: 99%